Cerebral blood flow rates in recent great apes are greater than in Australopithecus species that had equal or larger brains. Issue 1915 (13th November 2019) - Seymour, Roger S.; Bosiocic, Vanya; Snelling, Edward P.; Chikezie, Prince C.; Hu, Qiaohui; Nelson, Thomas J.; Zipfel, Bernhard; Miller, Case V.
Abstract : Brain metabolic rate (MR) is linked mainly to the cost of synaptic activity, so may be a better correlate of cognitive ability than brain size alone. Among primates, the sizes of arterial foramina in recent and fossil skulls can be used to evaluate brain blood flow rate, which is proportional to brain MR. We use this approach to calculate flow rate in the internal carotid arteries ( Q ˙ ICA ), which supply most of the primate cerebrum. Q ˙ ICA is up to two times higher in recent gorillas, chimpanzees and orangutans compared with 3-million-year-old australopithecine human relatives, which had equal or larger brains. The scaling relationships between Q ˙ ICA and brain volume ( V br ) show exponents of 1.03 across 44 species of living haplorhine primates and 1.41 across 12 species of fossil hominins. Thus, the evolutionary trajectory for brain perfusion is much steeper among ancestral hominins than would be predicted from living primates. Between 4.4-million-year-old Ardipithecus and Homo sapiens, V br increased 4.7-fold, but Q ˙ ICA increased 9.3-fold, indicating an approximate doubling of metabolic intensity of brain tissue. By contrast, Q ˙ ICA is proportional to V br among haplorhine primates, suggesting a constant volume-specific brain MR.